Is it only the thought that counts; or do gift cost, social approval, and relationship satisfaction matter too? - MALIK, Farah Binte Abdul (Institutional Knowledge at Singapore Management University, 2020)
This study investigated the effects of gift cost, social network (SN) approval, and relationship satisfaction on a gift receiver’s perception of the giver’s commitment to their romantic relationship. In addition to predictions of positive main effects (H1 to H3), it was predicted that relationship satisfaction would moderate the effects of gift cost (H4) and SN approval (H5). Participants were 227 undergraduates from Singapore who completed a survey online. A hierarchical moderated regression analysis was conducted, and the results supported all the hypotheses except H5. The novel findings were that receivers perceived their partners to be more committed when their SN members approved of the gift; and gift receivers who were less satisfied with their relationships were more influenced by gift cost.